Exploring colorectal cancer patients’ diagnostic pathways and general practitioners’ assessment of the diagnostic processes: a Danish survey study - Dorte E. Jarbøl; Sanne Rasmussen; Kirubakaran Balasubramaniam; Jesper Lykkegaard; Linda Juel Ahrenfeldt; Gitte B. Lauridsen; Peter Haastrup (Scandinavian Journal of Primary Health Care)
Introduction Colorectal cancer (CRC) is among the most common cancers and the prognosis of CRC is highly dependent on stage at diagnosis. Although many cases are diagnosed swiftly, there is still room for improvement.Aim We aimed to explore CRC diagnostic pathways, encompassing (1) place of initial contact; (2) associations with symptom presentations, sex, and age with events in the diagnostic process and initial referrals and (3) the general practitioner’s (GP’s) evaluation of the diagnostic processes.Methods All GPs in North-, Central-, and Southern Denmark were invited to fill in questionnaires for their listed patients diagnosed with cancer during the past two years.Results Among 1,032 recorded CRC patients, 65% had their initial contact in general practice, 5% within the out-of hours service, 10% in the hospital, and 20% were diagnosed based on screening. A total of 27% of CRC patients over 40 who initially presented in general practice were treated or referred on suspicion of another disease first, and 9% were reported to have had hesitated in seeking medical attention. Some 37% presented solely non-specific symptoms, increasing the odds of the GP advising watchful waiting (OR 2.48; 95% CI 1.06–5.81), treating or referring on the suspicion of another illness first (OR 2.57; 95% CI 1.76–3.75), wait due to normal findings (OR 2.11; 95% CI 1.16–3.85), or referring to diagnostic imaging (OR 3.07; 95% CI 1.63–5.79). The GPs assessed nearly one fifth of the diagnostic processes as poor.Conclusion Most CRC patients are diagnosed with initial presentation in general practice. Having non-specific symptoms is common and challenges timely diagnosis.